Entre conquistas e desafios: reflexão sobre a trajetória de um estudante de medicina e diálogos sobre ansiedade na graduação - Olher, Gabriel Romeiro (Universidade Federal de São Carlos, 2025)
This Undergraduate Thesis presents a longitudinal reflective narrative on the author’s experience throughout the six-year medical course at the Federal University of São Carlos, addressing both professional and personal development. The work traces the trajectory from moments prior to entering the university to the approach of graduation, in a narrative, critical, and subjective manner. It explores aspects such as entering the course during the COVID-19 pandemic, adapting to a new learning methodology, early involvement in patient care and assistance, and the choices and expectations that emerge near the end of the program. Throughout the narrative, the author engages in a reflective dialogue on anxiety, one of the most prominent feelings during the course. The thesis presents reflections on the challenges of anxiety within the program and the ways students cope with it. Additionally, the author discusses anxiety as something imagined to guide the formation of personality, but which, in practice, proved to be more of an obstacle than a support, creating a point of rupture regarding this ideal.
Between achievements and challenges: reflection on the journey of a medical student and discussions about anxiety during undergraduate studies
Keywords: Medicina; Narrativa; Educação médica; Educação superior; Relato de experiência; Ansiedade; Pandemia; CIENCIAS DA SAUDE::MEDICINA